EVALUATION OF THE THICKNESS AND THE LINEAR EXPANSION OF FISH CRACKERS PRODUCED BY SOME COTTAGE INDUSTRIES OF JEPARA DISTRICT (CENTRAL JAVA) - Ratna Ibrahim; Eko Nurcahya Dewi; Sumardianto . (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Fish crackers are locally known as “kerupuk ikan”. The quality of fish crackers depends on the thickness of the slice before frying, the percentage of linear expansion, and some other factors. So far, there was not any standard value of the thickness and the percentage of the linear expansion of good quality fish crackers in Indonesia yet. The objectives of this study were to gain some data on the thickness and the percentage of linear expansion of fish crackers and to compare the data with the estimated ideal value based on the reference data. Ten cottage industries in Jepara district chosen based on the proportional stratified randomized sampling method. The first grade fish crackers (according to the processor) were obtained as the samples from each of the cottage industries. Ten fish crackers of each sample were evaluated. The results indicated that the fish cracker samples were circular, the thickness varied from 1.0 to 3.85 mm. The average thickness of the samples was 2.77 mm which significantly thicker (p<0.01) than the estimated ideal thickness (1.50 mm). The percentage of linear expansion of the samples varied from 54.48 to 134.58 %